Division of Inheritance and Will: First Marital Children, Second Marital Wife (Literature Legal Review) - Selamat Lumban Gaol (Dinasti Research, 2024)
The purpose of this article is to make a positive contribution in promoting justice, understanding, and innovative solutions in the context of inheritance and testamentary divisions, particularly in situations involving children from first marriages and wives from second marriages. An in-depth article on the complexities of the division of inheritances and wills, in particular involving children from first marriages and wives from second marriages, qualitative research methods can be used. Qualitative research methods aim to understand phenomena in depth, exploring individual perspectives, values, and experiences related to the topic under study. Literature reviews of related scientific articles to provide reinforcement and ultimately the article offers a conceptual framework model of research results. The division of inheritances and wills is a complex topic, involving various aspects of law and social practice. In diverse societies, the process of inheritance sharing often reflects different cultural and religious values. However, in the context of globalization and modernization, there are challenges in harmonizing traditional practices with more inclusive modern laws. It is important to understand that the division of inheritances and wills is not only a legal issue, but also reflects complex social dynamics. Factors such as cultural norms, religious beliefs, and family structure can influence how inheritances are divided and wills are made.